Representasi Makna Denotasi Kekerasan Seksual Dalam Film Pendek Profil Pelajar Pancasila Episode Hujan Tak Akan Turun Selamanya - Fikri Ramadhan (CV. ITTC INDONESIA, 2024)
Sexual harassment is a form of sexual violence. Several cases of sexual violence in Indonesia occur online. From this case, the Indonesian Ministry of Education and Culture made a short film that raised the theme of online sexual harassment entitled